Gil Evans and his orchestra Live in Lugano - Evans, Gil 1912-1988 (TDK, 2005)
Gil Evans and his orchestra in concert
Recorded live at the Palazzo dei Congressi, Lugano, 27 January 1983. - Program notes in English, German and French in container. - Special feature: Gil Evans' biography
Keywords: Big band music; Jazz / 1981-1990